2014
DOI: 10.1074/jbc.m113.524512
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Promotes Macrophage-derived Foam Cell Formation by Up-regulating Cluster of Differentiation 36 (CD36) Expression

Abstract: Background: Endoplasmic reticulum (ER) stress is involved in the pathogenesis of atherosclerosis. Results: Pharmacological manipulation and siRNA treatment to reduce ER stress mitigate ox-LDL-induced CD36 up-regulation, which is promoted synergistically by ER stress inducer. Conclusion: ER stress promotes macrophage-derived foam cell formation by up-regulating CD36. Significance: ER stress-mediated macrophage-derived foam cell formation may be a novel target in the prevention of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 35 publications
6
65
0
Order By: Relevance
“…Approximately 60-70% of macrophage-derived foam cell formation is caused by scavenger receptor CD36-mediated ox-LDL uptake, which is a key factor to trigger ER stress response ( 28,29 ), and our recent study has shown that there is a positive feedback between ER stress and CD36 expression ( 27 ). Moreover, D4F downregulated CD36 expression in atherosclerotic lesions ( Fig.…”
Section: D4f Suppresses Ox-ldl Uptake and Cd36 Upregulation In Raw264mentioning
confidence: 90%
See 2 more Smart Citations
“…Approximately 60-70% of macrophage-derived foam cell formation is caused by scavenger receptor CD36-mediated ox-LDL uptake, which is a key factor to trigger ER stress response ( 28,29 ), and our recent study has shown that there is a positive feedback between ER stress and CD36 expression ( 27 ). Moreover, D4F downregulated CD36 expression in atherosclerotic lesions ( Fig.…”
Section: D4f Suppresses Ox-ldl Uptake and Cd36 Upregulation In Raw264mentioning
confidence: 90%
“…CD36, a class B scavenger receptor, plays a quantitatively crucial role in ox-LDL uptake and cholesterol accumulation in macrophages, whereas suppression of CD36 expression is able to significantly decrease the ability of macrophages to accumulate ox-LDL and reduce the development of atherosclerosis, suggesting that it could be an important target for therapeutic treatment ( 27,36,37 ). Our recent study indicated that CD36-mediated ox-LDL uptake in macrophages triggered ER stress response (ATF6, inositol-requiring kinase/endonuclease-1, and GRP78), which, in turn, played a critical role in CD36 upregulation and then enhanced the foam cell formation by promoting uptake of ox-LDL, indicating that there may be a positive feedback loop between ER stress and CD36 expression ( 27 ). In the present work, we indeed observed that D4F reduced serum ox-LDL level and CD36 expression in atherosclerotic lesions in apoE Ϫ / Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured LV-UFM1 macrophages were pretransfected with control siRNA (100 nM) or LXR siRNA (100 nM) for 24 h; they were then incubated with oxLDL (50 g/mL) for another 24 …”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Moreover, ER stress is a key regulator of macrophage differentiation and cholesterol deposition in the development of atherosclerosis 23) . Importantly, Yao et al 24) elucidated the exact relationship between ER stress and macrophage-derived foam cell formation. However, little is known about the interaction between UFM1 and macrophage foam cells.…”
Section: Introductionmentioning
confidence: 99%